2014
DOI: 10.4236/jamp.2014.25011
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties and Hyperfine Interactions in M-Type BaFe12-2xMoxZnxO19 Hexaferrites

Abstract: A series of M-Type barium hexaferrites with the general composition BaFe12-2xMoxZnxO19 were synthesized at 1100˚C by a simple wet chemical mixture route. The properties of the prepared samples were examined by X-ray diffraction, scanning electron microscopy, vibrating sample magnetometry, and Mössbauer spectroscopy. The diffraction patterns for all samples were found to agree well with the standard pattern of BaFe12O19 hexaferrite with no extraneous diffraction peaks. The products formed as well crystallized h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…This substitution for Fe ions may occur partially at the 3b VI site, which is responsible for the reduction in the strength of the superexchange interactions as argued in the context of discussing the magnetic data of this sample. [62,71,84]. The spectrum of the CoCr-Y sample, however, seems to be a combination of the spectra characteristic of M-type and Y-type hexaferrites, with modified hyperfine parameters due to Cr substitution.…”
Section: Ga-substituted Y-type Hexaferritesmentioning
confidence: 93%
See 1 more Smart Citation
“…This substitution for Fe ions may occur partially at the 3b VI site, which is responsible for the reduction in the strength of the superexchange interactions as argued in the context of discussing the magnetic data of this sample. [62,71,84]. The spectrum of the CoCr-Y sample, however, seems to be a combination of the spectra characteristic of M-type and Y-type hexaferrites, with modified hyperfine parameters due to Cr substitution.…”
Section: Ga-substituted Y-type Hexaferritesmentioning
confidence: 93%
“…In this study, Co 2+ ions were reported to occupy 6c VI octahedral sites in the T block exclusively. The distribution of metal ions over the different sites is determined from the relative intensities of the sub-spectral components, which, in principle, are proportional to the number of Fe ions in the corresponding sets of sites [62]. Fig.…”
Section: Mössbauer Spectroscopymentioning
confidence: 99%
“…Hard ferrites typically have a high value of Mr, which is about 50% of the saturation magnetization (Ms), therefore the reduced remnant magnetization (Mrs = Mr/Ms) must be nearly 0.5, and this is true for samples consisting of single-domains and random orientations of grains [32]. Table 3 shows that the values of Mrs are very close to 50%.…”
Section: Resultsmentioning
confidence: 97%
“…Many research groups prepared these ferrites and investigated the effect of the dopants on the magnetic properties of such M-type magnetic hexaferrites [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The hexaferrites are of great interest for applications in the microwave technology and others.…”
Section: Introductionmentioning
confidence: 99%
“…The substitution of cations at Fe 3+ or Ba 2+ sites is an efficient technique to alter the magnetic, physical, and electrical traits of hexaferrites (HFs) since magnetic and other features are correlated to the distribution of the doping ions on five crystallographic sites. Several studies have been done to substitute Fe 3+ ions by various cations, for example, Al +3 [8], Cr +3 [9], Eu-Nd [10], Ga +3 [11], Bi-Cr [12], Zr-Zn [13], Ti-Ru [14], and Mo-Zn [15], and significant changes were seen in magnetic and electrical features of substituted hexaferrites. Additionally, the substitution of the rare earth (RE) elements such as Tb +3 [16] and Nb-Dy [17] has been investigated to enhance the electromagnetic response of hexaferrites.…”
Section: Introductionmentioning
confidence: 99%